Blood glucose testing in the community: who are the users and do they have elevated blood glucose? - Jim Mann; Xiao Amelie Li; Andrew N Reynolds (CSIRO Publishing, 2020)
ABSTRACT INTRODUCTIONOn-the-spot blood glucose testing is a health service performed in public spaces to raise diabetes awareness and screen for elevated blood glucose levels. AIMTo describe the users of this service and the frequency of detecting elevated blood glucose. METHODSData collected at point-of-testing on a standardised form over 20 months in two regions of New Zealand were audited. Descriptive and simple inferential statistics report on population demographics and presence of elevated blood glucose (mmol/L). RESULTSData from 2156 individuals were audited. Most (1680, 78%) were female, the mean age was 52 years (standard deviation 18 years) and all major ethnic groups and socioeconomic quintiles were represented. For 53% of responders, this was their first blood glucose test. In total, 153 (7.1%) cases with elevated blood glucose were identified, including 94 who did not report a previous pre-diabetes or diabetes diagnosis. Blood glucose was not correlated with socioeconomic status (r=0.04; P=0.07), but weakly correlated with age (r=0.19; P<0.001). Blood glucose values did not appear to differ between ethnicities (P=0.052). Men had a higher mean value than women (P=0.003). People with elevated blood glucose access their general practitioner more often than people with normal blood glucose, irrespective of a diabetes diagnosis (P=0.002). DISCUSSIONOn-the-spot blood glucose testing is a health service accessed by a wide range of people, although more commonly by women than men. Future interventions targeting men may better engage them in health screening. Alongside awareness raising, on-the-spot community testing identified previously unknown elevated blood glucose levels at a rate of 1-in-22, and may lead to the earlier identification and treatment of prediabetes or diabetes.